Quality Instrument is Focused Reusability For Academic Information Systems Software - Sulistiani, Ino; Syafruddin Syarif; Yusran; Dewiani (Pusat Penelitian dan Pengabdian Pada Masyarakat Sekolah Tinggi Manajemen Informatika dan Komputer AKBA Makassar, 2023)
The usability-focused IS quality instrument is a conceptual model of a quality instrument that implements and focuses on standardizing usability behavior in a website software-based academic information system. Quality Structure along with Quality Factors and Quality Model Questionnaire Method which consists of the Basic Quality Questionnaire Method for AISS, Basic Quality Model Questionnaire Method and Usability Questionnaire Method are the research methods used. The purpose of this study is to propose an IS quality instrument that focuses on usability as a quality instrument that determines usability behavior in academic information system software, namely understandability, learnability, operability, attractiveness, and usability compliance. The usability-focused IS quality instrument is one of the quality assurance software quality instruments that has a high level of reliability and is required in every academic information system (AISS) software. So that a quality instrument is needed as a determinant of the quality of academic information system software that implements the quality model as an instrument system.